2020
DOI: 10.1021/acsbiomaterials.0c01078
|View full text |Cite
|
Sign up to set email alerts
|

6-Bromoindirubin-3′-oxime Promotes Osteogenic Differentiation of Periodontal Ligament Stem Cells and Facilitates Bone Regeneration in a Mouse Periodontitis Model

Abstract: Effective bone tissue engineering is important to overcome the unmet clinical challenges of periodontal tissue regeneration. Successful bone tissue engineering comprises three key factors: stem cells, growth factors, and scaffolds. 6-Bromoindirubin-3′-oxime (BIO) is an inhibitor of glycogen synthase kinase-3 (GSK-3) that can activate the Wnt signaling pathway by enhancing β-catenin activity. In this study, the effects of BIO on the proliferation, migration, and osteogenic differentiation of periodontal ligamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…In the present study, BIO treatment enhanced hDPSC osteogenic differentiation, as seen by increased ALP activity, odonto/osteogenic marker gene expression, and mineralised nodule formation. Similar results were found in other cell types, e.g., human PDLSCs [ 59 ], mouse PDLSCs [ 60 ], apical papilla stem cells [ 61 ], mouse DPs [ 62 ], hBMSCs [ 38 ], canine BMSCs [ 46 ], and mouse embryonic fibroblasts [ 63 ]. In contrast, it has been reported that LiCl-mediated Wnt signaling activation decreased the osteogenic differentiation [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, BIO treatment enhanced hDPSC osteogenic differentiation, as seen by increased ALP activity, odonto/osteogenic marker gene expression, and mineralised nodule formation. Similar results were found in other cell types, e.g., human PDLSCs [ 59 ], mouse PDLSCs [ 60 ], apical papilla stem cells [ 61 ], mouse DPs [ 62 ], hBMSCs [ 38 ], canine BMSCs [ 46 ], and mouse embryonic fibroblasts [ 63 ]. In contrast, it has been reported that LiCl-mediated Wnt signaling activation decreased the osteogenic differentiation [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 79%
“…In recent study, 6-Bromoindirubin-3'-oxime (BIO) was encapsulated into PLGA microspheres and loaded on HA hydrogel. Injected into the gingival sulcus of mice with experimental periodontitis, the PLGA-HA hydrogel system could release BIO via free diffusion and promote osteogenesis process 146 . Other studies demonstrated similar results associated with hydrogels incorporating SDF-1, BMP-2, NapFFY 147 .…”
Section: Biomaterials Science Accepted Manuscriptmentioning
confidence: 99%
“…The incorporation of PVA and natural polymers significantly compensated for the poor mechanical properties of natural polymer-based hydrogels and remained favorable for cytocompatibility and bioactivity [ 63 , 64 ]. PLGA is a non-toxic, degradable polymeric organic compound made by the polymerization of lactic acid and hydroxyacetic acid which has high biocompatibility and capsule- and film-forming properties as a carrier for cell implantation [ 65 ].…”
Section: Components Of Hydrogel In Periodontal Tissue Regenerationmentioning
confidence: 99%